Pengaruh digitalisasi pada sektor ekonomi kreatif di Indonesia - Amaliya, Denti (Maliki Interdisciplinary Journal, 2024)
Digitalization is the main driver of change in the global economy, including in Indonesia’s creative industry sector. This article analyzes the impact of digitalization on the growth and development of Indonesia’s creative industries. This study examines how digital technologies such as the internet, social media and e-commerce platforms have changed the way creative industry players operate, innovate and interact with the market. The findings show that digitalization not only improves operational efficiency and market access, but also opens up new opportunities for creative content and product creation. However, challenges such as the digital divide and the need to increase digital literacy still need to be overcome to maximize the potential of creative industries in the digital era.